If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 12) + -21x + 3 = 0 Reorder the terms: 6(12 + x) + -21x + 3 = 0 (12 * 6 + x * 6) + -21x + 3 = 0 (72 + 6x) + -21x + 3 = 0 Reorder the terms: 72 + 3 + 6x + -21x = 0 Combine like terms: 72 + 3 = 75 75 + 6x + -21x = 0 Combine like terms: 6x + -21x = -15x 75 + -15x = 0 Solving 75 + -15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75' to each side of the equation. 75 + -75 + -15x = 0 + -75 Combine like terms: 75 + -75 = 0 0 + -15x = 0 + -75 -15x = 0 + -75 Combine like terms: 0 + -75 = -75 -15x = -75 Divide each side by '-15'. x = 5 Simplifying x = 5
| 2z-1=15 | | (6s+5t)+(4t+8s)= | | 6(9n-7)=10n-(1-3n) | | 2(3x+2)+3(2+2x)=70 | | 7x+28=84 | | q=2k+2w | | -7z-2z=8z+7+z | | 22-x=3(c+6) | | -6x-2x+20=10 | | w/7-2=9 | | 5x^2-15=5x^2+2x | | 3x(-2/5)= | | (x^3-x+1)-(3x-1)= | | 5+4(a-2)=2(a-7)+1 | | 21-8k=-7(2k+3) | | -6x-18=-114 | | 2(-1-2x)+7x=6-5x | | 4x-1=2x-2 | | 66=24x+6y | | 10x+x+-6x=226 | | 5p+5-7=80 | | -9z-3z=-2z-3-4z | | 4c-2/5=6 | | 4(y+9)=3Y-14 | | (x^4)-(8x^2)-20=0 | | 9x-3x+90=9x+48 | | y=2(6+1)+5(3+3) | | 50x^2-288y^10=0 | | 8y-3=6y-17 | | x/4+9=6 | | (9x-23)+(5x+13)=x | | 10x+-6x=226 |